2004
DOI: 10.1042/bj20040965
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin 4-sulphotransferase-1 and chondroitin 6-sulphotransferase-1 are affected differently by uronic acid residues neighbouring the acceptor GalNAc residues

Abstract: C4ST-1 (chondroitin 4-sulphotransferase-1) and C6ST-1 (chondroitin 6-sulphotransferase-1) transfer sulphate from PAPS (adenosine 3'-phosphate 5'-phosphosulphate) to positions 4 and 6 respectively of the GalNAc residues of chondroitin. We showed previously that C4ST-1 purified from rat chondrosarcoma and recombinant C4ST-1 both transfer sulphate efficiently to position 4 of the GalNAc residues of DSDS (desulphated dermatan sulphate). We report here the specificity of C4ST-1 and C6ST-1 in terms of uronic acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Digestion with chondro-6-sulfatase of Tetra A or Tetra B was carried out for 5 h at 37°C in the reaction mixture containing, in a final volume of 25 l, 1.25 mol of Tris acetate buffer, pH 7.5, 2.5 g of bovine serum albumin, and 50 milliunits of chondro-6-sulfatase. After digestion of 35 S-labeled glycosaminoglycans or oligosaccharides with chondroitinase ACII or chondroitinase ABC, digestion with chondro-6-sulfatase or chondro-4-sulfatase was carried out twice successively in the reaction mixtures described above; first with 100 milliunits of enzyme for 17 h and second with 100 milliunits of enzyme for 5 h. Digestion with ␤-glucuronidase was carried out for 4 h at 37°C in a reaction mixture containing, in a final volume of 40 l, 35 S-labeled tetrasaccharide (ϳ40 nmol as galactosamine), 2 mol of sodium acetate buffer, pH 4.5, 20 nmol of 2-acetamido-2-deoxy-D-galactonic acid-1,4-lactone, 0.8 mol of sodium fluoride, and 18 units of ␤-glucuronidase. Under these conditions, removal of the nonreducing terminal GlcA was complete and no release of inorganic sulfate was observed.…”
Section: Volume 280 • Number 47 • November 25 2005mentioning
confidence: 99%
See 2 more Smart Citations
“…Digestion with chondro-6-sulfatase of Tetra A or Tetra B was carried out for 5 h at 37°C in the reaction mixture containing, in a final volume of 25 l, 1.25 mol of Tris acetate buffer, pH 7.5, 2.5 g of bovine serum albumin, and 50 milliunits of chondro-6-sulfatase. After digestion of 35 S-labeled glycosaminoglycans or oligosaccharides with chondroitinase ACII or chondroitinase ABC, digestion with chondro-6-sulfatase or chondro-4-sulfatase was carried out twice successively in the reaction mixtures described above; first with 100 milliunits of enzyme for 17 h and second with 100 milliunits of enzyme for 5 h. Digestion with ␤-glucuronidase was carried out for 4 h at 37°C in a reaction mixture containing, in a final volume of 40 l, 35 S-labeled tetrasaccharide (ϳ40 nmol as galactosamine), 2 mol of sodium acetate buffer, pH 4.5, 20 nmol of 2-acetamido-2-deoxy-D-galactonic acid-1,4-lactone, 0.8 mol of sodium fluoride, and 18 units of ␤-glucuronidase. Under these conditions, removal of the nonreducing terminal GlcA was complete and no release of inorganic sulfate was observed.…”
Section: Volume 280 • Number 47 • November 25 2005mentioning
confidence: 99%
“…For determining the activity toward various glycosaminoglycans, CS-A was replaced with 25 nmol (as galactosamine for chondroitin, CS-C, DS, and oligosaccharides, or glucosamine for heparan sulfate, completely desulfated N-resulfated heparin, and keratan sulfate) of glycosaminoglycans or oligosaccharides. When oligosaccharides were used as the acceptors, the reaction mixtures were applied directly to the Superdex 30 column as described below, and the 35 S-labeled oligosaccharides were separated from 35 35 S-labeled trisaccharides and tetrasaccharides with chondroitinase ABC, a strong condition was used under which digestion with chondroitinase ABC was carried out in the reaction mixtures described above three times successively; first with 120 milliunits of enzyme for 28 h, second with 100 milliunits of enzyme for 18 h, and finally with 100 milliunits of enzyme for 7 h. The new enzymes were added after heating the reaction mixtures at 100°C for 1 min. Digestion with chondro-6-sulfatase of Tetra A or Tetra B was carried out for 5 h at 37°C in the reaction mixture containing, in a final volume of 25 l, 1.25 mol of Tris acetate buffer, pH 7.5, 2.5 g of bovine serum albumin, and 50 milliunits of chondro-6-sulfatase.…”
Section: Volume 280 • Number 47 • November 25 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…Subcellular localization of these sulfotransferases is probably relevant to determining the order. The purified C6ST-1, C4ST-1, and GalNAc(4SO 4 ) 6-O-sulfotransferase (18 -20) as well as the recombinant C6ST-1, C4ST-1, GalNAc(4SO 4 ) 6-O-sulfotransferase, and uronosyl 2-O-sulfotransferase (12,16,17) have been found to be glycoproteins containing relatively abundant N-linked oligosaccharides. It has been reported that N-glycans contained in various glycoproteins are involved in protein folding, ER-associated protein degradation, intracellular trafficking, and production of functional proteins (21)(22)(23)(24)(25).…”
Section: Chondroitin Sulfate (Cs)mentioning
confidence: 99%
“…Increasing data have been accumulated showing that these sulfotransferases recognize not only the position of the sugar residue to which sulfate is transferred but also sequences or sulfation pattern of the component sugar residues. C4ST-1 preferentially transferred sulfate to GalNAc residues adjacent to the reducing side of the GlcA residue but not the IdoUA residue (16). Sulfation of position 6 of the nonreducing terminal GalNAc(4SO 4 ) in the unique sequence found in the nonreducing terminal of CS, GalNAc(4SO 4 )-GlcA(2SO 4 )-GalNAc(6SO 4 )-, by GalNAc(4SO 4 ) 6-O-sulfotransferase was markedly stimulated by the penultimate GlcA(2SO 4 ) residue (17).…”
Section: Chondroitin Sulfate (Cs)mentioning
confidence: 99%